Paleo-Pacific subduction-accretion: Evidence from Geochemical and U-Pb zircon dating of the Nadanhada accretionary complex, NE China - Zhou, J.-B.; Cao, J.; Wilde, Simon; Zhao, G.; Zhang, J.; Wang, B. (American Geophysical Union, 2014)
The Nadanhada Terrane, located along the eastern margin of Eurasia, contains a typical accretionary complex related to paleo-Pacific plate subduction-accretion. The Yuejinshan Complex is the first stage accretion complex that consists of meta-clastic rocks and metamafic-ultramafic rocks, whereas the Raohe Complex forms the main parts of the terrane and consists of limestone, bedded chert, and mafic-ultramafic rocks embedded as olistolith blocks in a weakly sheared matrix of clastic meta-sedimentary rocks. Geochemical data indicate that the Yuejinshan metabasalts have normal mid-ocean ridge basalt (N-MORB) affinity, whereas the Raohe basaltic pillow lavas have an affinity to ocean island basalts (OIB). Sensitive high-resolution ion microprobe (SHRIMP) U-Pb zircon analyses of gabbro in the Raohe Complex yield a weighted mean 206Pb/238U zircon age of 216 ± 5 Ma, whereas two samples of granite intruded into the complex yield weighted mean 206Pb/238U zircon ages of 128 ± 2 and 129 ± 2 Ma. Laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) U-Pb zircon analyses of basaltic pillow lava in the Raohe Complex define a weighted mean age of 167 ± 1 Ma. Two sandstone samples in the Raohe Complex record younger concordant zircon weighted mean ages of 167 ± 17 and 137 ± 3 Ma. These new data support the view that accretion of the Raohe Complex was between 170 and 137 Ma, and that final emplacement of the Raohe Complex took place at 137–130 Ma. The accretion of the Yuejinshan Complex probably occurred between the 210 and 180 Ma, suggesting that paleo-Pacific plate subduction was initiated in the Late Triassic to Early Jurassic.